Thermal management of a high speed permanent magnet machine for an aeroengine - La Rocca, A.; Xu, Z.; Arumugam, P.; Pickering, S.J.; Eastwick, Carol; Gerada, C.; Bozhko, S. (2016)
The paper describes the mechanical and thermal design of a high speed, high power density synchronous permanent magnet machine for an aero engine starter generator system with a power rating of 150 kW and maximum speed of 32,000 rpm. As both mechanical and thermal aspects have a direct impact on machine overall performance and weight reduction, a critical design optimisation was carried out. Intensive cooling is guaranteed by direct liquid oil-cooling of stationary components; a stator sleeve is also introduced into the airgap to prevent excessive windage. Thermal investigations were carried out by the means of Computational Fluid Dynamics (CFD) and Lumped Parameter Thermal Network (LPTN) analyses. Experimental validation also allowed the identification of most critical machine temperatures and the validation of the models developed. Finite Element Analysis(FEA) is used for the static structural analyses of the statorsleeve.